The Hypertext from a Different Perspective - Aleksander Piecuch (Maria Curie-Skłodowska University, Lublin, Poland, 2018)
In this article we return to the issues related to the technology of hypertext. New scientific reports from the field of neurobiology allow to look in a new light on the educational use of hypertext. Moreover, they sheds new light on the use of information and communication technologies on the intellectual development of man.